2011
DOI: 10.1152/jn.00467.2010
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory synaptic transmission and network activity are depressed following mechanical injury in cortical neurons

Abstract: In vitro and in vivo traumatic brain injury (TBI) alter the function and expression of glutamate receptors, yet the combined effect of these alterations on cortical excitatory synaptic transmission is unclear. We examined the effect of in vitro mechanical injury on excitatory synaptic function in cultured cortical neurons by assaying synaptically driven intracellular free calcium ([Ca(2+)](i)) oscillations in small neuronal networks as well as spontaneous and miniature excitatory postsynaptic currents (mEPSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 70 publications
5
44
0
Order By: Relevance
“…8 Campbell and colleagues 8 reported that 24 h post-TBI, there was a 21% loss in total spines on the AO dendrites of layer II/III cortical neurons, and loss of synaptic activity has also been reported in vitro, where stretch injury of hippocampal neurons results in a prolonged loss of excitatory synaptic transmission. 23 In the present study, we found that dendritic spine loss occurred over a wide area after a focal TBI, including a significant loss of dendritic spines in the contralateral cortex and hippocampus. We believe that our extensive loss of excitatory synapse sites is because CCI causes a much more severe injury than that seen with the unilateral fluid percussion injury model.…”
Section: Discussionsupporting
confidence: 55%
“…8 Campbell and colleagues 8 reported that 24 h post-TBI, there was a 21% loss in total spines on the AO dendrites of layer II/III cortical neurons, and loss of synaptic activity has also been reported in vitro, where stretch injury of hippocampal neurons results in a prolonged loss of excitatory synaptic transmission. 23 In the present study, we found that dendritic spine loss occurred over a wide area after a focal TBI, including a significant loss of dendritic spines in the contralateral cortex and hippocampus. We believe that our extensive loss of excitatory synapse sites is because CCI causes a much more severe injury than that seen with the unilateral fluid percussion injury model.…”
Section: Discussionsupporting
confidence: 55%
“…28 In vitro stretch injury of neurons also causes a prolonged loss of excitatory synaptic transmission. 29 In the present study, we focused our spine counts on layers II/III of the cortex and report that a single mTBI causes a 13% loss of spines in the AO dendrites in young male mice, with a greater spine loss occurring after mTBI on the same dendrites in aged male mice. Combined together, these studies of dendritic spines after TBI show that this is a common phenomenon that occurs in a severe TBI model (controlled cortical impact), 18,30 a moderate TBI model (FPI), 28 and our mild TBI model.…”
Section: Rapid But Temporary Synaptic Loss Occurs After a Single Mtbimentioning
confidence: 87%
“…An in vitro model of TBI mechanical with cultured cortical neurons, resulted in the membrane composition of glutamatergic receptors. That is, after stretch injury, calcium-permeable AMPA receptors were upregulated in plasma membranes [120,121]. …”
Section: Pathophysiology Of Memory Impairment After Tbimentioning
confidence: 99%